Realising sexual and reproductive health and rights of adolescent girls and young women living in slums in Uganda: a qualitative study - Majel McGranahan; Elizabeth Bruno-McClung; Joselyn Nakyeyune; Derrick Aaron Nsibirwa; Christopher Baguma; Christopher Ogwang; Francis Serunjogi; Judith Nakalembe; Marianna Kayaga; Sharifah Sekalala; Oyinlola Oyebode (Reproductive Health, 2021)
Plain Language Summary Every woman is entitled to good sexual and reproductive health. This involves being free from sexually transmitted infections, gender-based violence and maternal mortality, and able to access essential health services. In low and middle-income countries, adolescents comprise a fifth of the population, yet their sexual and reproductive health needs are often overlooked. Adolescent girls and young women are more likely to experience gender-based violence, sexually transmitted infections and poor access to sexual and reproductive health services. Those living in slums have even worse outcomes, but little evidence exists regarding the opportunities and barriers to improving sexual and reproductive health among adolescent girls and young women in a slum setting. In this study, we conducted focus groups and interviews with 21 adolescent girls and young women living in two Ugandan slums, 10 individuals with an essential role, for example, at state level, as well as 30 other stakeholders including healthcare workers, teachers, parents, district leaders and community support officers working with adolescent girls and young women. Results indicate that adolescent girls and young women lack information regarding their sexual health, what services are available and who and where to go if they experience violations such as sexual assault. In instances of sexual assault, fear and stigma prevented adolescent girls and young women from going to the police, and instead disputes were handled informally between families. Participants in our focus groups and interviews felt that education and training were needed, and that health services need to improve. Interventions are necessary to improve adolescent girls’ and young women’s sexual and reproductive health in this setting.